2021
DOI: 10.1021/acsaem.0c02797
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Interlayer-Expanded MoSe2/Nitrogen-Doped Graphene Heterojunctions for Ultra-Long-Cycling Rechargeable Aluminum Storage

Abstract: Owing to their low cost and abundant reserves, aluminum-ion batteries (AIBs) have been considered a potential candidate for future large-scale storage applications. However, AIBs are still in the stage of intensive research due to their cathodes of limited specific capacity, energy density, and cycling stability. In this work, interlayer-expanded MoSe2/nitrogen-doped graphene (MoSe2/N-G) heterojunctions with fewer layers and fine dispersion are synthesized by a facile hydrothermal method. Experimental verifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Similarly, the designed MoSe 2 /N-doped graphene composite exhibited the expanded interlayer spacing (from 0.63 nm of bulk MoSe 2 to 0.67 nm), which could improve the ion diffusion rate during the discharge/charge process. [134] In conclusion, interlayer spacing enlarging strategy has been demonstrated as an effective way to adjust the structure with the optimization of interlayer spacing, realizing the improved diffusivity/reaction kinetics and enhanced electrochemical performance. However, we notice that the interlayer spacing is rarely accurately regulated in previous reports.…”
Section: Enlarged Interlayer Spacingmentioning
confidence: 92%
“…Similarly, the designed MoSe 2 /N-doped graphene composite exhibited the expanded interlayer spacing (from 0.63 nm of bulk MoSe 2 to 0.67 nm), which could improve the ion diffusion rate during the discharge/charge process. [134] In conclusion, interlayer spacing enlarging strategy has been demonstrated as an effective way to adjust the structure with the optimization of interlayer spacing, realizing the improved diffusivity/reaction kinetics and enhanced electrochemical performance. However, we notice that the interlayer spacing is rarely accurately regulated in previous reports.…”
Section: Enlarged Interlayer Spacingmentioning
confidence: 92%
“…MoSe 2 was also investigated as the cathode for RABs by An and coworkers. 23 High-resolution transmission electron microscopy (HRTEM) analysis indicated that the d-spacing of MoSe 2 was increased from 6.7 Å to 7.2 Å after full discharge, and it returned to the original state after charging (Fig. 3g).…”
Section: Spinel or Layered Transition Metal Chalcogenidesmentioning
confidence: 99%
“…Theoretical calculations indicated that it would be extremely difficult if not impossible for Al 3+ to intercalate in transition metal oxides or sulfides. 7 Nevertheless, transition metal oxides, [8][9][10][11][12][13] chalcogenides, [14][15][16][17][18] and their carbon-based composites [19][20][21][22][23][24] have been reported as Al 3+ intercalation cathode materials. It must be pointed out that Al 3+ intercalation in the current chloroaluminate ionic liquid electrolytes involves chloroaluminate anions, since there are no simple Al 3+ cations existing in these electrolytes.…”
Section: Al 3+ Intercalation Cathode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, simple single-phase electrode materials are not enough to satisfy the requirement for reversible capacity and cycling stability [11] . Many researchers have done a lot of research on the composite and structural design of electrode materials, such as carbon coating [13][14][15] , heterostructure construction [1] and defective construction [16] , et al Conclusion, heterostructure construction has been proved to be an effective technical tool to improve the charge and electronic transfer kinetics and suppress the volume change during the electrochemical reaction process [17,18] . Mai et al [19] designed WS 2 /ZnS heterojunctions that shows enhance ions and electronic diffusion kinetics.…”
Section: Introductionmentioning
confidence: 99%